Colonial Williamsburg: Archaeology, Interpretation and Phenomenology - Peter Inker (EXARC Journal)
This paper stems from a keynote talk I was invited to give at the Archaeology for the People: Exhibition, Experience and Performance conference, in Kernave, Lithuania, in September of 2018. When I began investigating this conference I was unclear as to how well EXARC’s focus on experimental archaeology would blend with International Museum Theatre Alliance (Imtal)’s approach of museum theatre and interpretation. They seem after all, two very different disciplines. It could be said that experimental archaeology is about hard science, or at least scientific method–theory, experiment and conclusion, whereas Imtal’s work in museum theatre is concerned with a different set of skills and methodologies–performance, cultivating emotional connection, and interpretation. In the following I suggest they may have more in common than might initially be thought.